The Effect of Sharia Bank Financing, Zakat, and Education Expense, on Economic Growth and Human Development Index in Indonesia 2015-2019 - Indah Indria Wardani; Mohammad Nur Rianto Al Arif (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
Islamic bank financing, zakat, and education expenditure can increase Indonesia’s economic growth and Human Development Index (HDI). Islamic bank financing could be funding capital for the community. Zakat plays a role in wealth distribution, while education expenditure contributes by improving the quality of human resources. This study analysed the direct and indirect relationship between Islamic bank financing, zakat, and education expenditure to economic growth and HDI. Data were analysed using path analysis based on panel data for the period 2015-2019. The results showed that the Islamic bank financing, zakat and education expenditure had a significant positive effect on economic growth. Islamic bank financing, zakat, and education expenditure had a significant positive impact on HDI. At the same time, the indirect implications showed that Islamic bank financing, zakat, and education expenditure have a significant positive effect on HDI through economic growth. Pembiayaan perbankan syariah, zakat, dan belanja pendidikan menjadi instrumen yang dapat meningkatkan pertumbuhan ekonomi dan di Indonesia. Pembiayaan perbankan syariah dapat menjadi modal pendanaan bagi masyarakat, zakat berperan sebagai penyalur kekayaan, sedangkan belanja pendidikan dapat meningkatkan kualitas sumber daya manusia. Penelitian ini menganalisis hubungan langsung dan tidak langsung antara variabel pembiayaan bank syariah, zakat, dan pengeluaran pendidikan terhadap pertumbuhan ekonomi dan IPM. Analisis data menggunakan path analysis berdasarkan data panel untuk periode 2015-2019. Hasil penelitian menunjukkan bahwa pembiayaan bank syariah, zakat dan belanja pendidikan berpengaruh positif signifikan terhadap pertumbuhan ekonomi. Pembiayaan perbankan syariah, zakat, dan belanja pendidikan berpengaruh positif signifikan terhadap IPM. Sedangkan pengaruh tidak langsung menunjukkan bahwa pembiayaan bank syariah, zakat, dan pengeluaran pendidikan berpengaruh positif signifikan terhadap IPM melalui pertumbuhan ekonomi.